PENGALAMAN KOMUNIKASI PENGHUNI HUNTARA PETOBO PASCA BENCANA DI TENGAH PANDEMI COVID-19 - Wulandari, Dwi Rohma; Muslim, Adil (Kinesik, 2022)
This study aims to find out how the social life of the Petobo Shelter community as survivors of natural disasters, which until now still occupies the Shelter due to the liquefaction disaster on September 28, 2018 and is currently facing the Covid-19 pandemic situation. This study uses proxemic theory to view space and distance in the formation of communication, and the theory of violation of expectations. This research method is descriptive qualitative where in its approach, the researcher uses data conclusions and in-depth interviews. The results of this study indicate that the communication experience of the residents of the Petobo Shelter has adapted to the conditions of the Covid-19 pandemic. Interacting using a mask is not easy, apart from being required to speak a little louder than usual due to the muffled voice by the mask, the function of body movements is also to be a support for conveying messages due to voice conditions that are sometimes less audible and mouth movements are not legible. The quantity of communication itself is also reduced for communication activities during the Covid-19 pandemic, especially at the beginning of the pandemic when the number of cases of people exposed to it is high. Communication on a secondary basis or using media such as cellphones or gadgets is an option to communicate during the high number of cases of the spread of Covid-19 and also not to infect each other if there must be an in-person meeting.